The effects of foliar and nodes explants on callus induction of pogostemon cablin in-vitro culture by using plant growth regulator / Nursuria Md. Setamam and Norrizah Jaafar Sidik - Md. Setamam, Nursuria; Jaafar Sidik, Norrizah (Universiti Teknologi MARA Cawangan Pahang, 2020)
Pogostemon cablin is a traditional herb that commonly found in South East Asian. In Malaysia, this plant is well known as “pokok nilam”. Pogostemon cablin has been used widely in medicinal and cosmetic products due to the high content of patchouli alcohol. However, disease –free plant of Pogostemon cablin which required to be used for industrial, can only possible to obtained via in-vitro culture. The used of plant growth regulators such as auxin and cytokinin are able to yield the desire result for this micropropagation outcome. Nevertheless, the types of explants used also have major possibility in creating variation towards end of cultured product. Therefore, in this research, most common explants which are foliar and nodes were used as main interest of this study in order to induce callus by using cytokinin and auxin. After one month of observation, both foliar and nodes explant successfully were able to initiate callus in combination of both auxin and cytokinin as early as 8 days after incubation. However, single hormone of auxin was only able to initiate callus after two weeks for both type of explants. The experiment later, had been preceded with callus propagation which were done by using the most optimum callus product. These calluses were selected as they fit the criteria of desirable callus which are soft, friable and whitish in coloration as to support the high performance of callus propagation rate that were successfully obtained